Taxonomy of genus Orophyllus Beier, 1954 (Orthoptera: Tettigoniidae: Pseudophyllinae) - Xie, Hui-Cong; Wang, Han-Qiang; Li, Kai; He, Zhu-Qing (Zootaxa, 2021)
Only one species, Orophyllus montanus occurring in southern China is placed in Orophyllus. In this study, we studied samples from Hainan, Guangdong, Guangxi, Guizhou, Sichuan and Zhejiang enabling us to provide new information on this genus. Gene tree was constructed by COI gene. The results showed that there were new taxa other than the type species, namely O. grandivalvatus sp. nov. (巨瓣丽叶螽), O. nigrisartorius sp. nov. (黑缝丽叶螽), O. supeciliarilamellatus sp. nov. (眉板丽叶螽), O. guttatus sp. nov. (腹斑丽叶螽) All materials were deposited in Biological History Museum of East China Normal University (ECNU) and the Shanghai Entomological Museum, Chinese Academy of Sciences (SEM).